2021
DOI: 10.3390/app11177778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Biostimulants on Nutritional and Chemical Profiles of Almond and Hazelnut

Abstract: The increasing interest in natural foods with functional effects demands progressively higher production levels. Nonetheless, there is an orientation towards practicing more sustainable agriculture, free from environmentally harmful pesticides and fertilizers. Plant biostimulants, a class of bio-based agriculture products designed to improve crop development, represent a feasible alternative to chemical fertilizers, or, at least, an effective way of reducing the employed quantities. Herein, different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…There was no significant change in the fatty acid content of almond varieties with seaweed applications. It was reported that there was no change in fatty acids in the seaweed-treated Vairo' almond variety, and only linoleic acid amounted to 16.9% and a slight decrease (17.2%) was determined compared to the control (Pascoalino et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There was no significant change in the fatty acid content of almond varieties with seaweed applications. It was reported that there was no change in fatty acids in the seaweed-treated Vairo' almond variety, and only linoleic acid amounted to 16.9% and a slight decrease (17.2%) was determined compared to the control (Pascoalino et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Studies on seaweed in almonds are almost nonexistent. Studies related to the use of seaweed as a biostimulant exist in the literature (Pascoalino et al, 2021). Fatty acids are another of the most important factors that make up the quality of almonds.…”
Section: Introductionmentioning
confidence: 99%
“…These results were expressed as g 100g -1 of fw (fresh weight). Soluble sugar determination: Free sugars were determined by HPLC-RI system using a methodology described by (12). Freeze-dried samples were extracted with ethanol:water (80:20; v/v).…”
Section: Nutritional and Chemical Analysis Of Different Breadsmentioning
confidence: 99%
“…'Vairo' (syn. 'Vayro,' breeder's reference IRTAMB-A21-323) was to regions with hot summers, such as the Algarve and the NE of Portugal, where it has been widely cultivated (Queirós 2020;Pascoalino et al 2021). However, the agricultural practices and edaphoclimatic conditions such as low fertility soils or late frosts compromise the P. dulcis productivity and its biochemical profile (Queirós 2020;Pascoalino et al 2021).…”
Section: Experiments Site and Plant Materialsmentioning
confidence: 99%
“…The treatment of P. dulcis (foliage and rootstocks) with PBs or boron-based fertilizers can improve growth, stress tolerance, yield, and nutrient uptake (Saa et al 2015;Torres et al 2015;Mondragón-Valero et al 2019, 2020Pascoalino et al 2021).…”
Section: Experiments Site and Plant Materialsmentioning
confidence: 99%